Illumina sequencing and assessment of new cost-efficient protocol for metagenomic-DNA extraction from environmental water samples - Hassan,Mariam (2018)
Abstract In this study, the development and assessment of a modified, efficient, and cost-efficient protocol for mDNA (metagenomic DNA) extraction from contaminated water samples was attempted. The efficiency of the developed protocol was investigated in comparison to a well-established commercial kit (Epicentre, Metagenomic DNA Isolation Kit for Water). The comparison was in terms of degree of shearing, yield, purity, duration, suitability for polymerase chain reaction and next-generation sequencing in addition to the quality of next-generation sequencing data. The DNA yield obtained from the developed protocol was 2.6 folds higher than that of the commercial kit. No significant difference in the alpha (Observed species, Chao1, Simpson and PD whole tree) and beta diversity was found between the DNA samples extracted by the commercial kit and the developed protocol. The number of high-quality sequences of the samples extracted by the developed method was 20% higher than those obtained by the samples processed by the kit. The developed economic protocol successfully yielded high-quality pure mDNA compatible with complex molecular applications. Thus we propose the developed protocol as a gold standard for future metagenomic studies investigating a large number of samples.